2008
DOI: 10.1080/00498250802464685
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and minimizing time-dependent inhibition of cytochrome P450 3A in drug discovery: A case study with melanocortin-4 receptor agonists

Abstract: 1-[(2R)-2-([[(1S,2S)-1-amino-1,2,3,4-tetrahydronaphthalen-2-yl]carbonyl]amino)-3-(4-chlorophenyl)propanoyl]-N-(tert-butyl)-4-cyclohexylpiperidine-4-carboxamide (1) is a potent melanocortin-4 receptor agonist that exhibited time-dependent inhibition of cytochrome P450 (P450) 3A in incubations with human liver microsomes. In incubations fortified with potassium cyanide, a cyano adduct was identified by liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis as a cyanonitrosotetrahydronaphthalenyl deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Previous studies suggest that primary amines can be further oxidized to nitroso compounds, which can irreversibly inhibit enzymes leading to drug-drug interaction or toxicity [38].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that primary amines can be further oxidized to nitroso compounds, which can irreversibly inhibit enzymes leading to drug-drug interaction or toxicity [38].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, whether perpetrator/victim specific or enzyme specific, can be experimentally determined and reasonably scaled up. A recent report (54) illustrates the application of this approach in predicting the DDI magnitude in humans with the rat as the animal model. In this case, the investigating compound irreversibly inhibits both human and rat CYP3A-mediated metabolism of indinavir that is cleared in both species with CYP3A-mediated metabolism as the major elimination mechanism.…”
Section: Metabolism Modelsmentioning
confidence: 97%
“…However, potent reversible human CYP3A inhibitors, such as ketoconazole, appear to have reasonable cross-activity in many species, as shown by the comparable K i or IC 50 values determined in multiple species (51,52). Some mechanism-based CYP3A4 inhibitors also are effective for CYP3A of cynomolgus monkeys (53) and rats (54). Thus, DDIs caused by CYP3A inhibition may be reasonably reflected by multiple animal models.…”
Section: Metabolism Modelsmentioning
confidence: 98%
“…Previous studies have suggested that primary amine can be further oxidized to nitroso compounds, which can irreversibly inhibit enzymes, leading to drug-drug interaction or toxicity (Tang et al, 2008). However, M30 was not observed in HLM, so more work is needed to determine its formation in humans and the role of M30 in SQV toxicity.…”
Section: Discussionmentioning
confidence: 99%